Analysis of transfusion therapy during the March 2019 mass shooting incident in Christchurch, New Zealand. Issue 5 (12th March 2020) - Badami, Krishna G.; Mercer, Susan; Chiu, May; Yi, Ma; Warrington, Sue
Abstract : Background and objective: A mass casualty incident occurred in Christchurch in March 2019. Thirty‐seven patients with gunshot wounds were admitted. We describe and analyse the transfusion management of these casualties. Methods: Data on demographics, injury and laboratory characteristics, and transfusions are summarized using descriptive statistics. Relationships between variables are examined using Pearson's and Spearman's rank correlations. Univariate analysis of explanatory variables is performed to determine the best early predictors of transfusion requirements. The characteristics of massive transfusion and non‐massive transfusion cases are compared using the t ‐ and Mann–Whitney tests. Results: Sixty‐five per cent received transfusions. Initial Hb, platelet counts and clotting results were mostly normal. On average, each gunshot wound patient was transfused 4, 3·1, 1·2 and 0·4 units of RBC, FFP, cryoprecipitate and platelets, respectively, on the day. Base excess was the single best predictor of transfusion requirements. Conclusions: A greater proportion of those with gunshot wounds in this incident were transfused than in other such incidents. Transfusion requirements for patients varied but were generally modest. Blood component transfusion ratios were close to that recommended. The role of base excess as a predictor of transfusion requirements in patients with similar injuries needs more study.